ผลของระยะห่างระหว่างอักษร ความหนาของเส้นรบกวน และเงื่อนไขการใช้สี ต่ออัตรายืนยันความเป็นมนุษย์และอัตราความทนทานของแคปท์ชาข้อความ - ศุภาพิชญ์ ชูชาติ (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
Text-based CAPTCHA is a tool to asses if an online request is from a human user or from a software bot. Acceptable CAPTCHAs should be tolerant to automated software attack but still easy for humans to solve. The methods to measure the effectiveness of CAPTCHAs are (1) a human affirmative rate which means the rate through which users can identify the text that appears in CAPTCHAs correctly and (2) a robustness rate of CAPTCHAs which means the rate which through which CAPTCHAs are safe from automated software attack. Therefore, it is interesting to examine factors related to text-based CAPTCHAs. This study examined the effects of (1) character spacing, (2) thickness of disturbing line, and (3) color of disturbing line on the human affirmative rates and the robustness rates of CAPTCHAs. The study is based on a laboratory experiment. The analysis at 0.05 level indicates that the effects of character spacing and thickness of disturbing line are statistically significant on the human affirmative rate, but the effect of color of disturbing line is not significant. In addition, the effects of character spacing and thickness of disturbing line are statistically significant on the robustness rate of CAPTCHA, but the effect of color of disturbing line is not significant. In addition to extending knowledge of text-based CAPTCHA’s design, developers could apply the findings to define character spacing and thickness of disturbing line to design text-based CAPTCHAs that are easy for human but difficult for automated software attack.